Power series fitting of current-voltage characteristics of Al doped ZnO thin film-Sb doped (Ba 0.8Sr 0.2)TiO 3 heterojunction diode - N. Sirikulrat (2018)
The current-voltage (I-V) relationship of aluminum doped zinc oxide thin film-antimony doped barium strontium titanate single heterojunction diodes was investigated. The linear I-V characteristics are similar to those of the PN junction diodes. The linear conduction at a low forward bias voltage as predicted by the space charge limited current theory and the trap free square law at a higher forward voltage are observed. The overall current density-voltage (J-V) characteristics of the diodes are found to be well described by the Power Series Equation J=∑mCmVmwhere Cmis the leakage constant at particular power m with the best fit for the power m found to be at the fourth and fifth orders for the forward and reverse bias respectively. © 2011 Elsevier B.V. All rights reserved.